P-108 MAFLD-S SCORE: A CONVENIENT CLINICAL TOOL FOR PREDICTING MASLD IN PRIMARY CARE SETTINGS - JUAN ADRIÁN TORRES DÍAZ; ANTONIO OLIVAS MARTÍNEZ; JESÚS ALEJANDRO RUIZ MANRÍQUEZ; LUIS FEDERICO USCANGA DOMÍNGUEZ; LUIS CARLOS CHÁVEZ GARCÍA; ASHUIN KAMMAR GARCÍA; SOPHIA EUGENIA MARTÍNEZ VÁZQUEZ (Annals of Hepatology, 2024)
Conflict of interest: No Introduction and Objectives: Non-invasive methods for screening metabolic dysfunction-associated steatotic liver disease (MASLD) are gaining attention. A recent advancement in non-invasive screening is the MAFLD-S score, a tool that exclusively uses clinical data to predict the risk of MASLD.The aim is to evaluate the performance of the MAFLD-S score to identify individuals with MASLD in a cohort of apparently healthy individuals. Patients / Materials and Methods: A cross-sectional study was conducted including adults with unknown MASLD. A transient elastography was performed and hepatic steatosis was defined by a controlled attenuation parameter (CAP) > 248 dB/m. The MASLD criteria were assessed, and the MAFLD-S score, Fatty Liver Index (FLI) and Hepatic Steatosis Index (HSI) were calculated in each member of the cohort. The classification accuracy of these scores was evaluated through their areas under the receiver-operating characteristic (AUROC) curves and their calibration to predict the risk of MASLD was assessed graphically. Results and Discussion: A total of 521 participants were included, being 61% women, and the mean age was 41 years. The frequency of MASLD in the study population was 44.1%. The area under the ROC curve for MAFLD-S was 0.823 (95% CI, 0.788-0.858), for FLI was 0.841 (95% CI, 0.807-0.875) and for HSI was 0.822 (95% CI, 0.787-0.858). The calculated sensitivity for MAFLD-S score using the recommended threshold was 61% (95% CI 0.55-0.68) and specificity of 81% (95% CI 0.77-0.86), for FLI sensitivity was 62% (95% CI 0.56-0.68) and specificity was 82% (95% CI 0.78-0.87) and for HSI sensitivity was 85% (95% CI 0.80-.89) and specificity was 61% (95% CI 0.56-0.67). Conclusions: The MAFLD-S score, a tool that only uses clinical variables, confirmed to be a very good tool for screening MASLD in apparently healthy individuals in Mexico.